Reclaiming Uzbek Lands: Preventing Overgrazing With Sustainable Management and Legumes - Gafur, Gafurov (American Journal of Biology and Natural Sciences, 2025)
Contemporary food systems and consumption patterns lack sustainability on both domestic and global scales. The expected increase in demand for livestock goods in the future will necessitate not just more land for cultivation and enhanced yields, but an escalation in livestock production, as per current industry practices. Consequently, without shifts in consumption habits, there will be growing strain on limited assets over time. This is because livestock production relies on natural resources, exacerbating environmental degradation. Overgrazing not only diminishes species abundance but also results in considerable diversity loss within these ecosystems. Additionally, the degradation of grasslands can give rise to environmental issues like soil erosion, salinization, desertification, and wildfires. Nevertheless, grassland assets, being renewable, are crucial for preserving ecological stability and for upholding carbon equilibrium. To address these challenges, the report emphasizes the importance of soil stewardship in dry and semi-dry pastures. It suggests practices like moderate grazing, rotational management, and incorporating legumes to improve soil fertility and livestock health, supporting land restoration in Uzbekistan.